CONTENT OF EXPERIMENTAL WORK ON DEVELOPING CRITICAL THINKING IN STUDENTS THROUGH INTERNATIONAL ASSESSMENT PROGRAMS. (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The article examines the content of experimental work aimed at developing students' critical thinking through international assessment programs such as PISA, TIMSS, PIRLS, and others. The study focuses on methodologies and approaches that foster the development of analysis, synthesis, and evaluation skills among students of different age groups. It also discusses the outcomes of pilot projects and their impact on the educational process.